TLR4 Gene Polymorphisms Interaction With Ascaris Infection in Severe RSV Bronchiolitis - Buendía, Jefferson Antonio; Lindarte, Erika Fernanda; Polack, Fernando P. (Frontiers in Pediatrics, 2022)
Introduction : The identification of gene-environment interactions allows the recognition of groups with higher risk of morbidity. This study evaluated the interaction between the presence of TLR4 gene polymorphisms and Ascaris infection with severe bronchiolitis in a tropical Colombian region. Methods: We included all infants younger than 24 months hospitalized due to bronchiolitis in Hospital centers in the county of Rionegro, Colombia. To identify interaction between severe bronchiolitis and presence of TLR4 polymorphisms and Ascaris infection, we used log-binomial regression. Results: 417 infants were hospitalized due to bronchiolitis, of which 115 (27%) had severe bronchiolitis. In infants with RSV acute infection and positive anti-Ascaris IgE, TLR4 Asp299Gly was associated to low risk of severe bronchiolitis (OR 0.09, CI 95% 0.01-0.48). Conversely, in infants RSV negative with negative anti-Ascaris IgE, TLR4 Asp299Gly was associated with an increased risk of severe bronchiolitis (OR 14.5, CI 95% 2.2-96). Conclusion: The association between severe bronchiolitis and Ascaris infection in infants under 2 years old is mediated by TRL4 genotype.